University Student Experiences Using Tandem to Build English Speaking Confidence: Pengalaman Mahasiswa Universitas dalam Menggunakan Tandemuntuk Meningkatkan Kepercayaan Diri dalam Berbicara Bahasa Inggris - Fadiah Nur Amalia; Muhammad Dalimunte (Academia Open, 2025)
General Background: In the context of globalized education, English communication skills have become essential for university students. Specific Background: However, many learners struggle with self-confidence and self-awareness, which are critical for effective spoken interaction. Knowledge Gap: While digital language tools are widely used, limited research has explored the role of audio-based peer interaction in fostering these psychological and linguistic competencies. Aims: This study investigates how the Tandem application contributes to enhancing students’ self-confidence and self-awareness in English speaking. Results: Thematic analysis of in-depth interviews with five international EFL students revealed notable improvements in speaking confidence and reflective awareness of language use. Participants reported greater ease in communication, reduced anxiety, and a better understanding of their speaking patterns. Novelty: Unlike previous studies focusing on video or text-based platforms, this research emphasizes the unique pedagogical benefits of audio-only interactions and the influence of multicultural experiences on language development. Implications: The findings suggest that incorporating applications like Tandem can enhance learner autonomy, reduce performance pressure, and support holistic language acquisition. Educators are encouraged to integrate such tools into curricula to promote confident, reflective, and socially engaged language learners.Highlight : The Tandem app enhances students' speaking confidence by providing consistent practice with native speakers in low-anxiety settings. It fosters self-awareness through reflection, feedback, and recognition of language learning patterns and mistakes. Audio-only interaction in the app supports focus on verbal communication and reduces performance anxiety compared to video calls. Keywords : Tandem application, Self-confidence, Self-awareness, English Speaking, University Students